2015
DOI: 10.11152/mu.2013.2066.171.ayt
|View full text |Cite
|
Sign up to set email alerts
|

Sonoelastographıc assessment of the age-related changes of the Achilles tendon

Abstract: Aims: Tendons are crucial for optimal muscle force transfer and subject to changes with aging which may impair functional ability of elderly individuals. Achilles is the largest and the strongest tendon in the body; therefore it is an excellent site for the radiologic investigation of aging of tendons. Sonoelastography (SE) is a new ultrasound-based imaging technique that provides information on elastic properties and stiffness of tissues. The aim of our study was to investigate the age-related alterations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 23 publications
1
52
1
Order By: Relevance
“…As our study, Drakonaki et al did not find any difference with age or sex [12]. On the other hand, Turan et al found that the Achilles tendon was remarkably stiffer in elderly subjects compared to young subjects in all parts of the tendon examination [24]. Despite biomechanical studies demonstrating different viscoelastic properties with physical activity, we could not quantify the difference with sonoelastography.…”
Section: Discussioncontrasting
confidence: 53%
“…As our study, Drakonaki et al did not find any difference with age or sex [12]. On the other hand, Turan et al found that the Achilles tendon was remarkably stiffer in elderly subjects compared to young subjects in all parts of the tendon examination [24]. Despite biomechanical studies demonstrating different viscoelastic properties with physical activity, we could not quantify the difference with sonoelastography.…”
Section: Discussioncontrasting
confidence: 53%
“…Notably, both animal and human studies have shown evidence that aged tendon exhibits increased stiffness of the inter-fascicular matrix [2], an increase in collagen cross-linking [3, 4], and a reduction in collagen fibril crimp angle [34]. Although tendon elasticity measures in humans have produced conflicting evidence regarding an age-related decrease in tendon compliance [610, 35], the ambiguity may arise in part from methodological factors or from spatial definitions of the tendon, which may span regions of free tendon and aponeurosis. For example, one traditional ultrasound approach for measuring tendon elasticity involves tracking anatomical landmarks (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the age-related increase in free tendon shear wave speed would seem to reflect the material properties of the unloaded tissue, which could arise from increased stiffness of the interfascicular matrix [2]. Likewise, a recent study using a sonoelastography technique observed that older adult Achilles tendons exhibit less deformation with manual palpation [35], possibly reflecting greater transverse stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Arda et al 13 reported on elasticity values of Achilles tendons using a numeric scale in healthy volunteers, with a mean of 51.5 ± 25.1 kPa as Young modulus. During aging, Achilles tendon exhibited an increased stiffness when compared to young adults 14,15 ; however, other Authors did not find any correlation 16 . A positive correlation was found between tendon stiffness and BMI 17 ; results in smokers are controversial 17,18 .…”
Section: Normal Achilles Tendonmentioning
confidence: 75%
“…On the opposite side, diabetic patients with foot ulcers had thicker but softer tendons than healthy controls and diabetic patients without foot ulcers 41. In patients affected by ankylosing spondylitis, tendon pain was higher in patients with areas of softening. In particular, the distal third was the most commonly affected site and it was commonly associated with both bone erosion and enthesis enlargement 15,42 . Onal et al reported that patients with acromegaly had thicker tendon than healthy subjects, especially in active phase of disease.…”
Section: Other Pathologic Conditions Of the Achilles Tendonmentioning
confidence: 99%